A manual of recommended practice (Lansing, Michigan, 1980)
This book is the outgrowth of years of experience by Committee members and a compilation of research data and information on design, maintenance, and evaluation of industrial exhaust ventilation systems
Keywords: Y học nghề nghiệp,Occupational medicine,Nhà máy,Factories; Sưởi ấm và thông gió,Heating and ventilation